Dialogues with Audiovisual Archives - Giulia Taurino (VIEW Journal of European Television History and Culture)
This curated section1 explores the state of audiovisual archiving in Europe and North America, emphasizing the dynamic interplay between digitization efforts and the integration of artificial intelligence (AI) technologies within traditional archival workflows. Through interviews with archival professionals from key institutions, including the Latvian State Archive of Audiovisual Documents, Institut National de l’Audiovisuel, National Library of Sweden, Austrian Broadcasting Corporation, GBH, and the American Archive of Public Broadcasting, this partial ethnography of audiovisual archives provides insights into the histories, management structures, and mission statements that shape these heritage institutions. The findings reveal that while all institutions share the common aim to preserve audiovisual heritage, differences in their cultural contexts and operational frameworks influence their approaches to digital management and AI implementation. Key challenges identified include funding constraints and the necessity of maintaining archival integrity amidst technological transitions. Each archive’s strategy for integrating AI tools for metadata extraction and content analysis is discussed, highlighting both opportunities and challenges. The study ultimately underscores the importance of balancing traditional archival practices with innovative technological advancements to enhance the accessibility and discoverability of audiovisual collections, ensuring their preservation for future generations while addressing evolving digital landscapes.